2017
DOI: 10.1371/journal.pone.0175736
|View full text |Cite
|
Sign up to set email alerts
|

Shared processing in multiple object tracking and visual working memory in the absence of response order and task order confounds

Abstract: To understand how the visual system represents multiple moving objects and how those representations contribute to tracking, it is essential that we understand how the processes of attention and working memory interact. In the work described here we present an investigation of that interaction via a series of tracking and working memory dual-task experiments. Previously, it has been argued that tracking is resistant to disruption by a concurrent working memory task and that any apparent disruption is in fact d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 46 publications
4
28
0
Order By: Relevance
“…The first objective of the study was to validate whether combining 3D-MOT with a decision-making exercise could offer more challenging conditions while integrating broader contextual information. The dual-task condition produced a significant reduction in task performance in Experiment 1 and 2 which is consistent with most of the previous studies using dual-task MOT, 3D-MOT or spatial visual tests (Alvarez, Horowitz et al 2005, Allen, McGeorge et al 2006, Zhang, Xuan et al 2010, Thomas and Seiffert 2011, Faubert and Sidebottom 2012, Quevedo, Blázquez et al 2015, Lapierre, Cropper et al 2017. For example, Thomas & Seiffert (2011) observed a decrease in MOT performance between single and dual-task conditions (while walking) under high tracking load (≥ 3 targets).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The first objective of the study was to validate whether combining 3D-MOT with a decision-making exercise could offer more challenging conditions while integrating broader contextual information. The dual-task condition produced a significant reduction in task performance in Experiment 1 and 2 which is consistent with most of the previous studies using dual-task MOT, 3D-MOT or spatial visual tests (Alvarez, Horowitz et al 2005, Allen, McGeorge et al 2006, Zhang, Xuan et al 2010, Thomas and Seiffert 2011, Faubert and Sidebottom 2012, Quevedo, Blázquez et al 2015, Lapierre, Cropper et al 2017. For example, Thomas & Seiffert (2011) observed a decrease in MOT performance between single and dual-task conditions (while walking) under high tracking load (≥ 3 targets).…”
Section: Discussionsupporting
confidence: 89%
“…For example, Thomas & Seiffert (2011) observed a decrease in MOT performance between single and dual-task conditions (while walking) under high tracking load (≥ 3 targets). Likewise, Zhang and colleagues have concluded clear evidence that when a MOT task and a visual working memory task are performed concurrently, both tasks are disrupted as long as either task is sufficiently challenging to consume the resources available (Zhang, Xuan et al 2010, Lapierre, Cropper et al 2017. Interestingly, comparing Experiment 2 to Experiment 1 highlighted a greater dual-task cost when the additional task shared similar sensory modalities with the primary task.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has documented behavioral (Oksama & Hyönä, 2004;Lapierre et al, 2017) and neural evidence (Drew et al, 2011;Drew & Vogel, 2008;Vogel & Machizawa, 2004) that attentional tracking and working memory rely on overlapping cognitive mechanisms. Previous work has shown that a bilateral field advantage occurs when tasks require spatial attention or working memory, but not when they require feature-based attention (Alvarez, Gill, & Cavanagh, 2012) or working memory (Delvenne, 2005;Holt & Delvenne, 2014;Umemoto et al, 2010).…”
Section: Discussion: Experiments 2a and 2bmentioning
confidence: 99%
“…Although this evidence suggests that attentional tracking and working memory are at least partially distinct, there also appears to be a strong relationship between them. For instance, attentive tracking and working memory have strong correlations in performance (Oksama & Hyönä, 2004), high dual-task interference (Lapierre, Cropper, & Howe, 2017) and similar neural signatures (Drew et al, 2011;Drew & Vogel, 2008;Vogel & Machizawa, 2004). These findings suggest that although attentional tracking and working memory are partially distinct, the two processes likely share common components.…”
Section: Experiments 2a: Spatial Working Memory Crossovermentioning
confidence: 99%
“…Although this evidence suggests that attentional tracking and working memory are at least partially distinct, there also seems to be a strong relationship between them. For instance, attentive tracking and working memory have strong correlations in performance (Oksama & Hyönä, 2004), high dual task interference (Lapierre, Cropper, & Howe, 2017), and similar neural signatures (Drew et al, 2011;Drew & Vogel, 2008;Vogel & Machizawa, 2004). These findings suggest that, although attentional tracking and working memory are partially distinct, the two processes likely share common components.…”
Section: Experiments 2a: Spatial Working Memory Crossovermentioning
confidence: 90%